NEW TRENDS OF INTELLIGENT E-MARKETING AND CONSUMER BUYING BEHAVIOUR: A STUDY OF SELECTED UNIVERSITIES IN OSUN STATE, NIGERIA - Haorayau Bolaji Babalola; Saheed Ademola Lateef; Abu Abu Zekeri (STIM LASHARAN JAYA MAKASSAR, 2020)
Understanding the attitude and behavior of customers is essential for every company where consumers differ in attitudes towards product/service. The consumer buying behavior in today's information-saturated world is based on how a product/service is marketed. However, the rapid diffusion of technology anchored growth and challenges on e-marketing trends. For instance, despite the widespread and large-scale adoption of e-marketing around the world, one does not see this trend happening on a big scale in Nigeria. Therefore, this study examines the influence of e-marketing factors on consumer buying behavior in the Nigerian context with particular reference to the University students participating in online business. The study employed the quantitative method, where primary data were collected via online distribution of the questionnaires among 233 customers, specifically students of the Osun state Universities in Nigeria. Also, structural equation modeling using AMOS software was employed to examine the relationship and hypothesis testing. The findings of this study revealed that e-marketing is positively and significantly influence consumer buying behavior in the area of e-mail marketing, mobile marketing, and e-advertising factors. The study asserted that firms must engage the consumers using technology that are more likely acceptable by consumers in the present digital and customer-oriented era. Also, knowing fully the emerging technologies may furnish valuable insights for various stakeholders to work well in Nigeria. Finally, the new trends in e-marketing are recommended from a strategic and operational level in which different techniques ease the buying behavior of consumers.